An environmentally friendly fluorine-free sandwich coating based on a nonwoven fabric for efficient unidirectional water transport. Issue 94 (11th November 2021) - Zhang, Songnan; Li, Shuhua; Zhang, Zhibin; Huang, Jianying; Lai, Yuekun; Feng, Yan; Qian, Xiaoming
Abstract : A hydrophilic–hydrophobic sandwich PDMS-ormosil-PDMS@nonwoven fabric showed efficient unidirectional water transport performance and maintained excellent hydrophobic stability even after abrasion. Abstract : Medical research reveals that keeping the skin surface dry can effectively prevent a variety of fungal skin diseases. Therefore, it is of great practical significance to develop a light, thin, comfortable and breathable functional garment fabric with efficient one-way water transmission for people's requirements. Here, we successfully prepared a three-layer stacking sandwich coating to construct a Janus nonwoven material with efficient unidirectional water transport function, viz. PDMS-ormosil-PDMS@nonwoven fabric (PDMS-ormosil-PDMS@NF). Theoretical analysis showed that the loading of ormosil particles could enhance the surface roughness, while PDMS could strengthen the hydrophobic properties and bondability between the ormosil particles and fabric, thus acting as an environmentally friendly fluorine-free treating agent. The results revealed that the hydrophilic–hydrophobic PDMS-ormosil-PDMS@nonwoven fabric maintained excellent hydrophobic stability and good air permeability even after abrasion, which solved the existing problems of aerogel poor deposition and PDMS poor permeability, benefiting the application of textiles with unidirectional water transport performance.